The The potential of meat boiling water waste on plants: A systematic literature review - Erviana, Syeni; Fikri, Achmad Ali (Genbinesia Journal of Biology, 2024)
Boiling water waste from meat is often considered as useless waste, whereas it can be utilized as a potential source to support plant growth. The aim of this research is to identify the potential of meat boiling water waste as a nutrient source for plants, as well as to evaluate its impact on plant growth and soil quality. This study was conducted using a systematic literature review method, which involved the collection and analysis of various previous studies relevant to the researched topic. Through this literature review, it was found that meat boiling water contains essential nutrients such as nitrogen, phosphorus, potassium, and micronutrients that can enhance soil fertility and support plant growth. The research results indicate that the use of meat boiling water can contribute to plant growth, although there are potential negative impacts such as microbial contamination, nutrient excess or fat deposition if not managed properly. This research is expected to serve as an alternative organic fertilizer that can support sustainable agriculture, provided that it is managed correctly and considers risk factors. These findings provide new insights into waste management in the agricultural sector, with the hope of reducing dependence on chemical fertilizers and providing environmentally friendly solutions. In conclusion, meat boiling water waste has the potential to be a useful nutrient source for plants; however, careful management is required to minimize its negative impacts. Further research is needed to optimize the use of this waste in sustainable agriculture.